Implementation of land management under the conditions of marital law - Dorosh, O.; Dorosh, Y.; Fomenko, V. (Land Management, Cadastre and Land Monitoring, 2023)
On the basis of the analysis of the adopted changes to the land legislation and legal acts regulating land relations during the martial law, it was proved that their adoption was not done in a systematic way. It was found that the established special rules related to the implementation of land management and disposal of land plots for the period of martial law have different goals. It is about simplifying the procedure for disposal of agricultural lands – on the one hand, and on the other hand – activities in the field of land management, land cadastre and land valuation are complicated. It is substantiated that the changes that were made urgently highlighted the problem of imperfect land legislation in general, since the land legislation in force before the start of the war was designed exclusively for peacetime, because the issues of public access to sensitive information, such as: cartographic information, information on the purpose of land plots, names of land uses, names of subjects of land relations, etc.It has been established that the problem related to the provision of business entities and citizens under martial law for the provision of services for the preparation of land management documentation, topographical, geodetic and cartographic works has been resolved. For this purpose, the provision of special permits by the Security Service of Ukraine has been introduced.The urgent need for systematic adjustment of land legislation, both in the context of land management during the period of martial law and after its end (recovery period), as well as the need for harmonization of legislation in connection with European integration, which will become the basis for further research, is substantiated.Key words: land management, martial law, regulatory and legal support, management, special rules, land relations.
Keywords: land management; martial law; regulatory and legal support; management; special rules; land relations.